Finite element method (FEM) analysis of the force systems produced by asymmetric inner headgear bows - Geramy Allahyar; Kizilova Natalya; Terekhov Leonid (Sciendo, 2011)
Background: Extra-oral traction appliances were introduced more than a century ago and continue to be used to produce orthopaedic and/or dental changes in the maxilla. While force systems produced by asymmetric outer bows have been studied extensively, the force systems produced by asymmetric inner bows have been overlooked.